Pengaruh Efektivitas Promosi Melalui Instagram Dan Inovasi Produk Terhadap Keputusan Pembelian - Henny Sulistiyowati; Nuri Purwanto (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2021)
This study aims to determine the effect of the effectiveness of promotion through instagram and product innovation on purchasing decisions for Gembul Banana products. The study was conducted because the results of several previous researchers found that product innovation and promotion are key factors in influencing purchasing decisions. The tight business competition that comes from businesses for similar products or substitute products, requires a business to always move faster and creatively to come up with new ideas in order to attract the attention of consumers. The method used in this research is descriptive explanatory method. Analysis of the data used using multiple linear regression analysis model. The population in this study were all buyers of Gembul Banana products by taking a sample of 101 respondents, and taking the sample using accidental sampling technique. The results showed that the effectiveness of promotion through instagram and product innovation had a positive effect on purchasing decisions for Gembul Banana products. Based on the results of this study, it is suggested to Gembul Banana business owners to be more serious in managing Gembul Banana social media, especially in posting photos, endeavor to post photos that are interesting and in accordance with consumer desires, not just photos and uploads on social media. In addition, it is also recommended that the logo of the company should be included on the packaging, not only in the form of a yellow box that is identical to a banana, but a logo must be included so that consumers can remember the product.